The Obstetrical Care and Delivery Experience of Women with Epilepsy in the MONEAD Study - McElrath, Thomas F.; Druzin, Maurice; Van Marter, Linda J.; May, Ryan C.; Brown, Carrie; Stek, Alice; Grobman, William; Dolan, Mary; Chang, Patricia; Flood-Schaffer, Kellie; Parker, Lamar; Meador, Kimford J.; Pennell, Page B.; for the MONEAD Investigator Group (American Journal of Perinatology, 2022)
Objective We examined mode of delivery among pregnant women with epilepsy (PWWE) versus pregnant controls (PC). We hypothesize that PWWE are more likely to deliver by cesarean.Study Design The Maternal Outcomes and Neurodevelopmental Effects of Antiepileptic Drugs (MONEAD) study is an observational, prospective, multicenter investigation of pregnancy outcomes funded by the National Institute of Health (NIH). MONEAD enrolled patients from December 2012 through January 2016. PWWE were matched to PC in a case:control ratio of 3:1. This analysis had 80% power to detect a 36% increase in cesarean frequency assuming a baseline rate of 30% among PC at an α = 0.05.Results This report analyzed 331 PWWE (76%) and 102 PC (24%) who gave birth while enrolled in the study. PWWE and PC had similar rates of cesarean delivery (34.7 vs. 28.6%; p = 0.27). Of women with cesarean, rates of cesarean without labor were similar between groups for those delivering in recruitment hospitals (48.2 vs. 50.0%) but in nonrecruitment hospitals, cesarean rates without labor were over two-fold higher among PWWE than those of PC (68.8 vs. 30.8%; p = 0.023). Receipt of a cesarean after labor did not differ for PWWE compared to PC or by type of antiepileptic drug among the PWWE.Conclusion These findings suggest that the obstetrical experiences of PWWE and PC are similar. An interesting deviation from this observation was the mode of delivery with higher unlabored cesarean rates occurring among PWWE in nonrecruitment hospitals. As the study recruitment hospitals were tertiary academic centers and nonrecruitment hospitals tended to be community-based institutions, differences in perinatal expertise might contribute to this difference.Key Points
Keywords: cesarean; epilepsy; seizure; prenatal care